Foreword to the Special Section on the 8th ACM/EG Expressive symposium (Expressive 2019). (April 2020) - DiVerdi, Stephen; Kaplan, Craig S.; Forbes, Angus G.; Catalano, Chiara Eva
Highlights: Real-world technical challenges for expressive rendering in VR animation. Combining neural style transfer with patch based synthesis for improved details. Improved efficiency of neural style transfer through adversarial training. Graphical abstract: